Optimalisasi Fungsi Mediasi terhadap Kasus Perceraian Andre Taulany: Analisis Teoritis dan Yuridis terhadap Fungsi Mediasi dalam Sistem Peradilan Agama Indonesia - Muhammad Riyan Ahsani; Silva Samanta; Musleh Harry (Kartika: Jurnal Studi Keislaman, 2025)
This study addresses the issue of the suboptimal function of mediation in divorce cases in Religious Courts, which in practice often remains a procedural formality. Using the case study of Andre Taulany's divorce as a representation of complex domestic conflict involving public figures and social pressures, this study uses normative legal methods with a statutory and case-based approach to analyze the implementation of mediation based on Supreme Court Regulation Number 1 of 2016, Law Number 1 of 1974 concerning Marriage, Law Number 7 of 1989 concerning Religious Courts, and the Compilation of Islamic Law (KHI), and is linked to the concept of ishlah in Islamic law and modern conflict resolution theory. The results show that although procedurally, mediation has been implemented in accordance with legal regulations, substantively, it has not been able to optimally fulfill its reconciliatory and transformative functions due to the influence of psychological factors, social pressure as a public figure, and institutional limitations of mediators. Therefore, a more integrative, humanistic, and relationship-restoring model is needed, rather than merely fulfilling procedural obligations.